THE USE OF UNMANNED AERIAL VEHICLES FOR ORTHOPHOTO PLANS - Zatserkovnyi, V.; Tishaiev, I.; Komarova, U. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
For many years, traditional aero photography has been an effective instrument to solve geodesic, geophysical, geological cartographic and monitoring tasks. However, the prime cost of usage of aviation carriers for local large-scale survey of the area is relatively high and has a number of limitations. That is why the actual task is to find the way to decrease prime cost of photographing. One of the promising approaches to get geodesic basis is method of remote cartographing using unmanned aerial vehicles (UAVs). In today’s world aerospace has been developing rapidly with the help of UAVs, which proved to be extremely cost effective and convenient in terms of saving time and labor costs for photographing works. Aerial photography of the area, carried out with the help of UAV can be used in many fields and spheres, in particular in geodesy, topography and cartography. The controlling of UAV is possible to execute with the help of a smartphone, tablet or software or satellite connection. UAVs can be launched using missiles, catapults or manually and are able to carry various types of materials, video equipment or even fertilizers for agricultural purposes. The creation of an orthophoto plan that allows to accurate measure of territories, to establish or actualize the borders (boundaries) of any settlement (village, town, region), to execute environmental and agronomic land evaluation was considered in the article. On the basis of received orthophoto maps it is possible to conduct highly-precise topographic mapping and thus to create Master Plan and plan of territory development. Algorithm UAV (air drones) data processing targeted to get orthophoto plan is described in the article. It is identical for the majority of software that is used for such purpose. The difference is only in peculiarity of work with each of it.